Auditor's going-concern reporting: Reporting decision and content of the report - Nina Sormunen (Copenhagen Business School (CBS), 2012)
The going-concern context has been the subject of much research and discussion for many years at both academic and professional levels. The International Standard on Auditing (ISA) 570 stipulates that the auditor should consider the appropriateness of managements' use of the goingconcern assumption and to evaluate whether there are material uncertainties with respect to entity's ability to continue as a going concern. Regardless of what is stated in the financial statement, the auditor should comment on going-concern uncertainty in the audit report if there is a doubt about firm's ability to continue as a going concern. There is strong evidence that the auditor's going-concern decision is a complex task with extensive consequences. The primary purpose of this thesis is to empirically provide significant basis to get better understanding of the challenging nature of the auditor's going-concern reporting. This thesis deals with different aspects of auditor's going-concern reporting and contributes mainly to the line of auditing research.
hdl:10398/8490
Keywords: 650